Co-occurring illicit fentanyl use and psychiatric disorders in emergency department patients - Allie Downs; Lauren Walter; Richard Shelton; Li Li (Scientific Reports)
Abstract This paper sought to describe the characteristics of emergency department (ED) patients with illicit fentanyl use and concurrent psychiatric disorders, as studies within this population of patients is limited. ED patients with a fentanyl-positive urine drug screen were identified, and patient characteristics, medical histories, and test results were extracted. Among the fentanyl positive drug screens of ED patients, the majority were between the ages of 25 and 44, male, white, and uninsured. Additionally, more than one third of these patients had concurrent psychiatric disorders with mood disorders being the most prevalent, followed by psychotic disorders. Patients with co-occurring psychiatric disorders were found to have higher rates of marijuana use, repeat ED visits and/or hospital admissions at six months, and more admissions to psychiatry inpatient settings compared to those patients without co-occurring psychiatric disorders. Concurrent other substance use and rates of buprenorphine prescribing at discharge were not different between the groups; however, rates of naloxone provision at discharge were lower in patients with co-occurring psychiatric disorders. This cohort demonstrates higher healthcare recidivism and utilization.